Introducing Problem- Based Learning as an Effective Learning Tool to Medical Students: An Approach in Bangladesh (Bangladesh Journal of Medical Education, 2021)
Background: Bangladesh, A country with scintillating beauty of nature burdened with a dense population. Along with infectious diseases, tropical diseases are also prevalent here with a higher trend of non- communicable diseases as a result of industrialization. Practicing and prescribing as a doctor is a quite challenging profession here particularly when to deal with vast rural populations in a low resource facility. Medical education system is well developed in Bangladesh which follows traditional curriculum of teaching learning. Students are not accustomed with problem-based learning as it does not exist in curriculum. In order to confront with diverse disease pattern and overloaded population in this arduous backdrop of Bangladesh, problem- based learning can be a very effective tool for preparing medical students as an efficient, self- directed and insightful prescriber. This study was a primary step to introduce problem- based learning (PBL) to medical students of Bangladesh to evaluate the effectiveness of PBL in context of Bangladesh.Methods: Around 117 students of 4th year from 6 different medical colleges were randomly assigned for this study. Among them, half of the students attended PBL session for three days on a topic of Pharmacology and other students participated traditional lecture class. Following classes, odds ratio of performance was determined. MCQ, SAQ and total scores of assessment were compared. Comparison of scores was also done between male and female students of PBL group.Results: PBL students performed better than the LBL students. Odds ratio of their assessment performance was 252.08; with 95% confidence interval and lower range 53.89 and upper range 1179.28. The odds ratio showed strong association between PBL and student performance in Bangladesh context. Mean of total score was 30.7 ± 4.3 in PBL group and 17.2 ± 4.8 in LBL group. Total score was significantly higher (p= 0.000) in PBL group. Mean SAQ score in PBL and LBL group was 17.2 ± 2.2 and 5.3 ± 1.9 respectively which was extremely significant (p= 0.000). MCQ score mean was 13.4 ± 3.4 in PBL group versus 11.8 ± 3.7 in LBL group which was significantly higher in PBL group (p= 0.02). Among PBL group, total score and SAQ score was significantly higher in female students over male students.Conclusion: Significant findings of this study revealed PBL as an effective tool in Bangladesh context. Thereby, it is recommended from this study to take approaches for further study and initiative to incorporate PBL in curriculum as well.Bangladesh Journal of Medical Education Vol.12(1) 2021: 22-31